(3SHY ebGdGJ ef cdGe GHj GdaJhM CMeO Hf eMeO Hf GdSQj GdHZOGOj GdeYQha HGHf GdUdGMs - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3HYO GdHSedI ebGdI GdTjN GHj GdaJhM aj GdTcd GdQGHY ef CTcGd GdbjGS GdMedj hgh GdeTcd GdefShH Edi LGdjfhS s
(3BNQgG (B:s
(3hPdc Tcd eSJbje GdNWhW , aEPG de jcf TF BNQ UGQ gPG MjfFP Cf jYde Gdcdj hMjfFP GjVkG JfhY cdj aGdcdj EPG CLhO s
(3Vef eLehY , JQJjHgG (B: 7s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs